Tiger vanquished LTTE's story - Narayan Swamy, M R (New Delhi SAGE Publications, 2010)
Collection of news stories and commentaries penned by the author from 2003 to 2009.
Keywords: Sri Lanka -- History -- Civil War, 1983-2009.; Sri Lanka -- Politics and government -- 21st century